Comparison of digital elevation models based on high resolution satellite stereo imagery - Qayyum, A. (IEEE Computer Society, 2015)
In this paper, we analysed and compared the digital elevation model (DEM) based on high resolution QuickBird and Pleiades satellite stereo images. 3D maps were generated for objects like trees near poles of power transmission lines using satellite stereo images. This study was very challenging due to weather condition, hilly and non-uniform terrain at Kota kina balu in East Malaysia. First we require the geometric accuracy of these two sensors for 3D mapping of the area of interest. Also we require accurate Digital elevation model for better height calculation of vegetation/trees near power poles. For these purposes, we evaluated the accuracy of DEM using high resolution satellite stereo imagery. The comparison was made based on RPC coefficients and ground control point's measurement (GCP). Results shown that the Pleiades satellite sensor is feasible for generating the elevation model for small area. This shows that Pleiades sensor can be used for monitoring the vegetation near poles of high transmission power lines based on the satellite stereo images. Â© 2015 IEEE.